(untitled) (UNED Research Journal, 2016)
The common house gecko, Hemidactylus frenatus, is a native of Indonesia that has rapidly colonized new environments. Normally it is found in human constructions, but it can also invade natural environments and is causing the displacement and extinction of some native lizards, mostly in oceanic islands. In the Pacific reserve of Isla del Coco (Costa Rica) we captured nine specimens with sticky traps and direct capture. Theridium spp. accounted for 54% of its stomach contents (25,7% were unidentified remains and 18,8% Hymenoptera).